ANALISIS IMPLEMENTASI INTERNATIONAL WHALING COMMISSION DI JEPANG PADA MASA PEMERINTAHAN SHINZO ABE (2015-2018) - Pailo, Brigitha Leovani; Burhanuddin, Agussalim (JIMR : Journal Of International Multidisciplinary Research, 2024)
This study analyzes the implementation of the International Whaling Commission (IWC) in Japan during the Shinzo Abe administration (2015-2018) with a focus on scientific and commercial whaling programs. This study uses library research. Whaling constitutes an inherent part of Japanese society with historical and cultural roots that span over centuries. The Japanese government initiated a new special permit whaling program in Antarctica, called the New Scientific Whale Research Program in the Antarctic Ocean, replacing the JARPA II program. This initiative intends to enhance the precision of data on the biology and ecology of Antarctic minke whales, as well as explore the composition and dynamics of marine ecosystems in Antarctica. In November 2016, the Japanese government presented a proposal for a specialized permit program in the North Pacific, named the New Scientific Whale Research Program in the Western North Pacific. After leaving, Japan continued commercial whaling in its territory. This study highlights the complexity of a country's political, economic, and cultural dynamics in responding to international regulations, as well as its impact on whale conservation and marine ecosystems.